Peran Kompetensi Sumber Daya Manusia untuk Mendorong Inovasi Produk dan Kinerja UMKM - Widodo, Sri; Puspitasari, Anggraini Dwi; Handono, Wiyasto Dwi (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
Micro, Small, and Medium Enterprises (MSME) are the backbone of economic development for every economy. They contribute to local economic development through household wealth creation, job creation, and poverty reduction. MSME in Indonesia are an important sector for the country's economy but often face unique challenges. Focusing on this specific context, this research provides insights tailored to the business environment in Indonesia. The aim of this research is to present a comprehensive analysis of MSME strategies in Indonesia, focusing on human resource competencies, product innovation, and MSME performance. The research sample was selected using purposive sampling techniques, resulting in 83 respondents. The data were analyzed using multiple linear regression analysis. The findings of this research prove that human resource competencies and product innovation can enhance MSME performance. These findings underline the importance of strategic decision-making in shaping MSME performance outcomes in Indonesia. Alignment between strategy and innovation plays a role in improving MSME performance. Strategies focusing on human resource competencies, product uniqueness, and quality require innovation to add value to products and customers. The novelty of this research considers the resource-based theory approach in the relationship between human resource competencies, product innovation, and MSME performance.